Evaluation of a biphasic medium for blood cultures. - Hall, M M (1979)
A study comparing the recovery of microorganisms from a transiently vented biphasic brain heart infusion medium bottle and a vacuum bottle containing tryptic soy broth demonstrated that growth was initially detected on the slant of the biphasic bottle or on a routine subculture of either broth in nearly 50% of instances. All organisms were isolated equally well in both bottles, with the exception of Staphylococcus aureus, which was isolated significantly more frequently from the biphasic bottle, and anaerobic bacteria, which were isolated significantly more frequently from the tryptic soy broth bottle.